APPLICATION OF ANALYTICAL HIERARCHY PROCESS (AHP) IN SELECTING OPTIMAL THERAPY FOR OVARIAN CYST DISEASE - Sakinah, Gita (Journal of Mathematics and Scientific Computing With Applications, 2023)
Ovarian cysts are one of the common health disorders in women that require proper diagnosis and treatment. Unfortunately, ovarian cyst patients face challenges in determining the optimal therapy for treating ovarian cysts. So, the aim of this research is to develop a decision model using the Analytic Hierarchy Process (AHP) to select the optimal therapy for ovarian cyst treatment. By analyzing 4 criteria, this model identifies the most optimal factors influencing therapy selection, including hormonal treatment, laparoscopic surgery, laparotomy surgery, and alternative medicine. The findings indicate that alternative therapy has the highest priority in terms of recovery time, while hormone therapy excels in cost criteria. The consistency ratio (CR) in the analysis is below the established threshold (? 0.1), indicating the reliability of the calculation results. The AHP method has proven effective as a decision-making tool in the selection of ovarian cyst therapy. This research provides insights for healthcare practitioners in selecting the appropriate treatment method and suggests further studies to explore additional factors influencing medical decisions.